Dodsworth in New York - Egan, Tim, 1957- (Houghton Mifflin, 2007)
When Dodsworth sets out for adventure, including a stop in New York City before going to Paris, London, and beyond, he does not expect a crazy duck to stow away in his suitcase and lead him on a merry chase.